Wife's Accountability in Islamic Household Accounting - Diah Ayu Gustiningsih; Mediaty Mediaty; Alimuddin Alimuddin; Andi Kusumawati (Universitas Muhammadiyah Sorong, 2022)
This study was conducted to find the form of a wife's responsibility in Islamic household accounting, with a transcendental phenomenological approach. Transcendental phenomenological analysis techniques include 5 stages, namely: noema, noesis, epoche, intentional analysis and eidetic reduction. The results of the study indicate that the responsibility carried out by the wife in an Islamic household carried out in her household is accountability with the aim of maintaining self-esteem and maintaining self-image of her husband, for the expenses made, where there are 6 responsibilities, namely: income, maintenance, ZIS , consumption, investment, and saving into 4 responsibility centers, namely: revenue center, cost center, investment center and wealth center.